Pemeriksaan dan Pemberian Obat Anemia Kepada Ibu Hamil di Desa Kota Pari Pantai Cermin - Nasri Nasri; Vera Estefania Kaban; Kasta Gurning; Chyntia Glori Tania (Yayasan Literasi Sains Indonesia, 2022)
The incidence of anemia in pregnant women carries a great risk because the fetus's need for iron and oxygen supply during development requires iron. This community service activity aims to examine and administer anemia drugs or blood boosters to pregnant women and provide education related to anemia and important nutritional intake for pregnant women to prevent risk factors for anemia. A total of 36 pregnant women patients checked themselves, with 12 in the first trimester, 15 in the second trimester, and 9 in the third trimester. A total of 7 people in the first trimester experienced anemia (19.44%), 10 people in the second trimester (27.77%), and 5 people in the third trimester (13.88%). The rest do not have anemia. This can be due to the fact that the intake of balanced nutrition and foods rich in iron is sufficient during pregnancy. Iron intake during pregnancy in the first trimester is recommended at as much as 0.8 mg/day, while in the second and third trimesters, as much as 6.3 mg/day. Thus, it is hoped that the imparted knowledge and information will be adhered to in order to limit the risk of anemia in pregnant women so that the process of pregnancy until birth will proceed without incident.